Reconsidering the Cultural Geographies of State and Non State Spaces - Hatib r Abdul Kadir (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2016)
Abstract In Indonesia, the societies have a long history as a runaway society and fugitive from the state-making projects. Many historical accounts prove that people escape from the state projects, such as corvee labor, wars, diseases and epidemics, conscriptions, slavery, taxes, violence, warfare, diseases, and poverty. In general, this paper describes the state-society relations and examines the meaning of the non-governed society. This paper questions what distinguishes between govern and non-governed society, what kind of social economy and cultural life of non-governed society that distinguishes from a governed state? To answer these questions, this paper explores the distinction of the governed and the non-governed society, which live in the different geographical areas. This paper explains the distinctions and frictions between lowland and highland society in Indonesia, in terms of social economy, kinship, political organization, and religion. In the last reflection, the author argues that non governed society is not only people who live in the upland and far from the centralized bureaucracy, rather they also live in the middle of dense population of a town and even under a most centralized and autocratic regime. Keywords: Geography of the Highland and Lowland, non Governed Society, Resistance, Anarchism.